The therapeutic mechanism of transcranial iTBS on nerve regeneration and functional recovery in rats with complete spinal cord transection - Liu, Jia-Lin; Wang, Shuai; Chen, Zheng-Hong; Wu, Rong-Jie; Yu, Hai-Yang; Yang, Shang-Bin; Xu, Jing; Guo, Yi-Nan; Ding, Ying; Li, Ge; Zeng, Xiang; Ma, Yuan-Huan; et al. (Frontiers in Immunology, 2023)
Background After spinal cord transection injury, the inflammatory microenvironment formed at the injury site, and the cascade of effects generated by secondary injury, results in limited regeneration of injured axons and the apoptosis of neurons in the sensorimotor cortex (SMC). It is crucial to reverse these adverse processes for the recovery of voluntary movement. The mechanism of transcranial intermittent theta-burst stimulation (iTBS) as a new non-invasive neural regulation paradigm in promoting axonal regeneration and motor function repair was explored by means of a severe spinal cord transection. Methods Rats underwent spinal cord transection and 2 mm resection of spinal cord at T10 level. Four groups were studied: Normal (no lesion), Control (lesion with no treatment), sham iTBS (lesion and no functional treatment) and experimental, exposed to transcranial iTBS, 72 h after spinal lesion. Each rat received treatment once a day for 5 days a week; behavioral tests were administered one a week. Inflammation, neuronal apoptosis, neuroprotective effects, regeneration and synaptic plasticity after spinal cord injury (SCI) were determined by immunofluorescence staining, western blotting and mRNA sequencing. For each rat, anterograde tracings were acquired from the SMC or the long descending propriospinal neurons and tested for cortical motor evoked potentials (CMEPs). Regeneration of the corticospinal tract (CST) and 5-hydroxytryptamine (5-HT) nerve fibers were analyzed 10 weeks after SCI. Results When compared to the Control group, the iTBS group showed a reduced inflammatory response and reduced levels of neuronal apoptosis in the SMC when tested 2 weeks after treatment. Four weeks after SCI, the neuroimmune microenvironment at the injury site had improved in the iTBS group, and neuroprotective effects were evident, including the promotion of axonal regeneration and synaptic plasticity. After 8 weeks of iTBS treatment, there was a significant increase in CST regeneration in the region rostral to the site of injury. Furthermore, there was a significant increase in the number of 5-HT nerve fibers at the center of the injury site and the long descending propriospinal tract (LDPT) fibers in the region caudal to the site of injury. Moreover, CMEPs and hindlimb motor function were significantly improved. Conclusion Neuronal activation and neural tracing further verified that iTBS had the potential to provide neuroprotective effects during the early stages of SCI and induce regeneration effects related to the descending motor pathways (CST, 5-HT and LDPT). Furthermore, our results revealed key relationships between neural pathway activation, neuroimmune regulation, neuroprotection and axonal regeneration, as well as the interaction network of key genes.